Empowering Education: Transformational Leadership Creates Inspiring Work Climates to Boost Teacher Performance - Nurrizayani, Nurrizayani; Niswanto, Niswanto; Usman, Nasir (JURNAL AL-TANZIM, 2024)
The principal's leadership plays a crucial role in shaping the work dynamics of teachers, necessitating a strong commitment to offering clear direction and active support to the teaching staff. Furthermore, a favorable work environment encourages effective communication between the principal and the teachers. This research examines the effect of transformational leadership and work climate on school teacher performance. Employing a quantitative approach with an ex post facto design, the study involved 70 respondents selected randomly from six schools with A and B accreditation. Data were gathered using validated questionnaires, and the hypothesis was tested through multiple linear regression analysis. The findings revealed that transformational leadership significantly influenced teacher performance, with a t-value of 3.698 and a significance level of 0.005. Additionally, the work climate had a notable effect, reflected by a t-value of 2,842 and a significance level of 0.005. When combined, transformational leadership and work climate considerably impacted teacher performance, as evidenced by an F-value of 29.357 and a significance level of 0.000. This research underscores the critical role of principals as motivating leaders and emphasizes the importance of fostering a supportive work environment to boost teacher performance in schools.